Optimization of Metal Oxide Nanostructures via Two-Step Hydrothermal Synthesis - Anthony, L.S. (Institute of Electrical and Electronics Engineers Inc., 2019)
Metal oxide nanostructures have been commonly utilized as biosensors for the early detection and treatment of diseases. However, the translation of biosensors from research laboratories to clinical applications has remained limited due to degrading accuracies and irreversible reactions that result in long response and recovery times. Recent breakthroughs have highlighted the potential of transition metal oxides as a viable solution. In this work, we synthesize several transition metal oxide nanostructures using a novel combination of the sol-gel process and hydrothermal method. Through physical characterization, numerous nanostructures were obtained; particularly nickel oxide nanoflakes, cobalt oxide nanoparticles, manganese oxide nanomolars and nanowires as well as zinc oxide nanorods and nanoflakes. Among the four materials, zinc oxide and manganese oxide followed the general trend of resistivity but also displayed the greatest resistance due to their high density of nanostructures. The development of these materials will provide a new avenue for researched to understand the mechanisms involved in fabricating nanostructures as well as stimulate broader interest in improving biosensor capabilities. Â© 2019 IEEE.